2017
DOI: 10.1177/1526602817732316
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes After Endovascular Repair and Open Surgery to Treat Immunoglobulin G4–Related and Nonrelated Inflammatory Abdominal Aortic Aneurysms

Abstract: Though sample sizes were rather small, this pilot study suggested that EVAR-treated IgG4+ IAAA patients have a higher risk of persistent symptoms and increases in PAF, sac diameter, and IgG4 levels. Therefore, OS should be preferred for complete recovery. Frequent monitoring of the postoperative serum IgG4 is necessary following EVAR in IgG4+ patients to detect these complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Based on these findings, before surgery, a high serum IgG4/IgG ratio, high MMP-9 concentration, and high monocyte and eosinophil counts would be useful in determining the IgG4-AAA-up subgroup. Furthermore, for patients with IgG4-AAA with these hallmarks, we recommend OSR to prevent the progression of aneurysm [18]. This is because, as previously reported, OSR could provide complete recovery for patients with IgG4-AAA along with longer survival and fewer complications [7][8][9][10][11]18].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Based on these findings, before surgery, a high serum IgG4/IgG ratio, high MMP-9 concentration, and high monocyte and eosinophil counts would be useful in determining the IgG4-AAA-up subgroup. Furthermore, for patients with IgG4-AAA with these hallmarks, we recommend OSR to prevent the progression of aneurysm [18]. This is because, as previously reported, OSR could provide complete recovery for patients with IgG4-AAA along with longer survival and fewer complications [7][8][9][10][11]18].…”
Section: Discussionmentioning
confidence: 71%
“…However, several recent studies on patients with IgG4-AAA treated by EVAR have reported severe complications leading to death, such as aneurysmal enlargement to rupture or aortoduodenal fistula and aortic dissection [14][15][16][17]. Furthermore, another study, although with a small sample size, compared the prognosis of patients with IgG4-AAA without steroid medication between those treatment by EVAR and those treated by OSR and indicated that approximately half of patients with IgG4-AAA who underwent EVAR were at risk for persistent symptoms, PAF progression, and enlarged aneurysm sac, whereas those treated by OSR did not experience these complications [18]. Considering the severe outcomes of several patients with IgG4-AAA after EVAR [14][15][16][17], a preoperative criterion to predict them would be crucial to select the surgical procedures, and the following postoperative markers would need to be assessed to provide additional treatment for their early recovery.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study that described the long-term outcomes of IgG4-RD patients who underwent surgery for AAA reported that re-dilation of the AAA-sac, PAF progression, and worsening of clinical symptoms were frequently observed in IgG4-AAA patients who had undergone EVAR but that these were not seen in patients treated with open surgical repair (OSR). 17 Among the explanations, residual pressure from the stent graft may promote persistent inflammation in the intact aortic wall. Whereas OSR for AAA results in a complete interruption of the blood flow in the aorta, the residual AAA-sac remaining after EVAR may ultimately become filled with blood, particularly in cases of endoleaks.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the post-therapeutic clinical course might differ between IgG4-related and non-IgG4-related vascular lesions. Fourth, it may be anticipated that the post-operative clinical course may differ from that of the non-IgG4-related cases, in terms of progression of fibrosis, dilation of vessels, and persistence of symptoms [115]. Last, we might be able to alleviate organ hypoperfusion with less invasive medical therapy [11,28], although this possibility should be examined in further analysis.…”
Section: The Value Of a Diagnosis Of Igg4-related Periaortitis/periarmentioning
confidence: 99%